The prospects of wooden building construction in Malaysia: current state of affairs - Ab Latib, Hazirah; Cheong, Lum Wai; Halis, Rasmina; Mohamad Kasim, Mohamad Roslan; Lee, Yan Yi; Ratnasingam, Jegatheswaran; Ioras, lorin (NC State University, 2019)
The objective of this study was to evaluate the extent to which the practicing architects in Malaysia were familiar with timber products as a construction material. The materials consumption data was extracted from the Construction Industry Development Board (CIDB) database and was used to conduct a survey among 189 respondent architects. The results indicated that the architects were familiar with common timber products such as plywood, fiberboard, particleboard, and laminated veneer lumber. Correlation analysis of awareness and knowledge against the rate of utilization of these timber products was significant. Furthermore, the most important deterrent factors for the use of timber products in building construction in Malaysia were the high cost, poor durability, restrictive building codes and by-laws, as well as the low fire resistance. More aggressive promotion of timber products as a potential construction material is advisable to be undertaken when the goal is to boost the material’s use in the construction industry. Policy makers may also consider providing financial incentives to increase timber products utilization in building construction in Malaysia.